Essential guide to operations management : concepts and case notes - Bamford, David R.; Forrester, Paul L., 1961- (Hoboken, NJ : John Wiley & Sons, 2010)
This work is aimed at practising managers, who need to make decisions, manage change and design working processes within a strategic framework. The framework and supporting case vignettes allow the practitioner to grasp essential concepts relatively quickly in a range of different operational contexts.
Operations management in context -- Designing business processes -- Designing products & services -- Transfer of technology -- Controlling enterprise resources -- Developing lean operations -- Managing projects -- Managing operations strategically -- Managing quality systems -- Improving the operations -- Making it all work!
Includes bibliographical references (pages 211-212) and index.
Print version record.
John Wiley and Sons
Keywords: Production management; Production -- Gestion; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Industrial Engineering; BUSINESS & ECONOMICS -- Production & Operations Management; Production management; Operations Management